CXCL12 Enhances Human Neural Progenitor Cell Survival Through a CXCR7‐ and CXCR4‐Mediated Endocytotic Signaling Pathway123. (22nd October 2012) - Zhu, Bing; Xu, Dongsheng; Deng, Xiaobei; Chen, Qiang; Huang, Yunlong; Peng, Hui; Li, Yuju; Jia, Beibei; Thoreson, Wallace B.; Ding, Wenjun; Ding, Jianqing; Zhao, Lixia; et al.
Abstract: Chemokine CXCL12 is widely expressed in the central nervous system and essential for the proper functioning of human neural progenitor cells (hNPCs). Although CXCL12 is known to function through its receptor CXCR4, recent data have suggested that CXCL12 binds to chemokine receptor CXCR7 with higher affinity than to CXCR4. However, little is known about the function of CXCR7 in hNPCs. Using a primary hNPC culture system, we demonstrated that CXCL12 promotes hNPC survival in the events of camptothecin‐induced apoptosis or growth factor deprivation, and that this effect requires both CXCR7 and CXCR4. Through fluorescence‐activated cell sorting analysis and immunocytochemistry, we determined that CXCR7 is mainly localized in the early endosome, while CXCR4 is more broadly expressed at the cell surface and on both early and recycling endosomes. Furthermore, we found that endocytosis is required for the prosurvival function of CXCL12. Using dual‐color total internal reflection fluorescence microscopy and immunoprecipitation, we demonstrated that CXCR7 quickly trafficks to plasma membrane in mediating CXCL12 endocytosis and colocalizes with CXCR4 after CXCL12 treatment. Investigating the molecular mechanisms, we found that ERK1/2 endocytotic signaling pathway is essential for hNPC survival upon apoptotic challenges. Consistent with these findings, a significantly higher number of apoptotic NPCs were found in the developing brain of CXCR7 knockout mice. In conclusion, CXCL12 protects hNPCs from apoptotic challenges through CXCR7‐ and CXCR4‐mediated endocytotic signaling. Since survival of hNPCs is important for neurogenesis, CXCR7 may become a new therapeutic target to properly regulate critical processes of brain development. STEM CELLS 2012;30:2571–2583